2013
DOI: 10.12691/ajmbr-1-4-2
|View full text |Cite
|
Sign up to set email alerts
|

Xanthine Dehydrogenase Inhibition Stimulates Growth and Development of Human Brain Derived Cells

Abstract: Background: Reactive Oxygen Species (ROS) play a critical role in development of number pathologies. Xanthine Oxidase (XO) as well as the Xanthine Dehydrogenase (XDH) are two enzymes responsible for the last steps of purine catabolism, hydroxylation of a wide variety pyrimidines, and the initiation of ROS synthesis. In our current experiments we have analyzed whether exogenously added allopurinol, not only the inhibitor of XO but also XDH, is capable for in vitro human brain derived cells growth, development a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In our studies, we have shown that inhibition of XO by its classical inhibitor might initiate regenerative processes in neuronal cell culture by the inhibition of purine catabolism by feedback mechanism as well as by the inhibition of XOgenerated ROS [26][27][28]. On the other hand, we also propose the utility of such albumin particles for the treatment of stroke.…”
Section: Discussionmentioning
confidence: 91%
“…In our studies, we have shown that inhibition of XO by its classical inhibitor might initiate regenerative processes in neuronal cell culture by the inhibition of purine catabolism by feedback mechanism as well as by the inhibition of XOgenerated ROS [26][27][28]. On the other hand, we also propose the utility of such albumin particles for the treatment of stroke.…”
Section: Discussionmentioning
confidence: 91%